The impact of digital divide on infromation literacy development among the secondary school students in Malaysia / Jeffri Idris - Idris, Jeffri (2010)
This study attempts to investigate the relationships between digital divide and information literacy development. It is significant for reasons that it provides the current situations of digital divide in the country, students' information literacy levels and ICT use among them. The focus is whether having an access to digital technology particularly computer and the Internet, has affected the development of information literacy. This is based on the understanding that the use of ICT is important to information seeking activities as almost all types of information are available digitally and that sucking information using the ICT has become a need. Acquiring information using, the ICT enables people to get the right information effectively, efficiently and simultaneously develops their information literacy skills. Unfortunately, not all have the opportunity to get access to the ICT especially those in rural areas. The research concentrates on the secondary school students as the population. This survey research used questionnaire to Identify students': a) views on the importance of ICT, b) information skills background knowledge, c) access to the ICT, d) ICT skills and e) levels of information literacy skills. Eighty school were identified randomly from all over the country. Each school was given fifteen sets of questionnaire to be administered. There were a total of 1200 questionnaires sent and this study used 920 of them for analysis. SPSS 16.0 for Windows was used for data analysis to perform the descriptive and inferential analyses. The study found the existence of digital divide between rural and urban schools, and between lower secondary and upper secondary students. No digital divide existed between gender types. It also found that must students' information literacy skills were low. Relationships were discovered between information literacy development and: a) ICT skills, b) information skills background knowledge, c) frequency of accessing information sources. No relationships existed between information literacy skills and: a) students’ geographical areas, gender and form levels, b) home ICT access, c) frequency of using the ICT. The findings also revealed that most students learnt information skills and had a positive view on the importance of ICT. Also, most of them had computer access at home but only a small number had the Internet access.